2004
DOI: 10.1029/2003ja010320
|View full text |Cite
|
Sign up to set email alerts
|

Plasmaspheric plumes: CRRES observations of enhanced density beyond the plasmapause

Abstract: [1] CRRES plasma wave receiver density data were used to study the distribution and properties of dense plasmaspheric-like plasma observed outside the plasmapause. Our study indicates that outer plasmaspheric structure, often called plasmaspheric plumes, blobs, tails, or detached plasma regions, can exist at all local times under all levels of geomagnetic activity. Of the 558 CRRES orbits that had at least one clearly defined plasmapause, 169 (or 30%) had plasmaspheric-like density structures at higher L shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 26 publications
7
84
2
Order By: Relevance
“…Broad plumes, by definition occurring at large L only, have low densities. Such results are in agreement with previous studies, especially with the CRRES study by Moldwin et al (2004) concerning the L−MLT distribution and geomagnetic indices results. An early OGO 5 study also found that "detached plasma regions", now understood to be plumes, are mostly observed in the afternoon sector (Chappell, 1974).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Broad plumes, by definition occurring at large L only, have low densities. Such results are in agreement with previous studies, especially with the CRRES study by Moldwin et al (2004) concerning the L−MLT distribution and geomagnetic indices results. An early OGO 5 study also found that "detached plasma regions", now understood to be plumes, are mostly observed in the afternoon sector (Chappell, 1974).…”
Section: Discussionsupporting
confidence: 83%
“…We obtain 782 plume crossings, which correspond to 15% of the plasmasphere passes with data (5222 passes). This is smaller as compared to other studies: Moldwin et al (2004) found a proportion of 30% of clear plasmasphere passes with plume structures. There are three possible explanations.…”
Section: Data Selectioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Soon after their observation, there were a number of modeling studies that suggested they were formed by dynamic sunward convection electric fields peeling away the outer layers of the plasmasphere forming the bulge and long tails towards the dayside magnetosphere (e.g., Chen and Wolf, 1972;Chen and Grewbowsky, 1978;Lemaire, 2000;Nishida, 1966). Figure 1 shows an observation of three successive orbits of the Combined Release and Radiation Effects Satellite (CR-RES) in the same local-time sector, showing the appearance of density structure beyond the main plasmapause (Moldwin et al, 2004). CRRES had a 10 h orbit, so significant differences in the high-density distribution are observed from one orbit to the next as well as significant outward radial motion of the innermost plasmapause location.…”
Section: Plasmaspheric Plumementioning
confidence: 99%
“…Plasmaspheric plumes are large-scale density structures that are usually connected to the main body of the plasmasphere, and extend outward (e.g., Elphic et al, 1996;Ober et al, 1997;Sandel et al, 2001). Plasmaspheric plumes have been detected by in-situ and ground-based instruments (e.g., Chappell et al, 1970;Carpenter et al, 1992;Foster et al, 2002;Moldwin et al, 2004;Goldstein et al, 2004;Darrouzet et al, 2006Darrouzet et al, , 2009b. Dense (>10 cm −3 ) plasmaspheric plumes and/or cold ions at the magnetopause have been observed (Chappell, 1974;Gosling et al, 1990;McFadden et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%